Effect of capillarity on the acoustics of partially saturated porous rocks - Qi, Qiaomu (Curtin University, 2015)
Capillarity is known to control the fluid distribution in partially saturated rocks. This thesis explores the effect of capillarity on acoustic signatures within the framework of Biot's poroelasticity theory. The results show that capillary phenomena may have a significant impact on seismic velocity, attenuation and reflectivity. A workflow based on the proposed theory is developed for quantitative interpretation of time-lapse seismic signatures. The results can be useful for accurate estimation of saturation from seismic data.